2016
DOI: 10.1080/14992027.2016.1226521
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric hearing aid management: a demonstration project for using virtual visits to enhance parent support

Abstract: Virtual visits provided benefits to families including flexibility and timely access to support. The ability to collect data logging information more frequently was important for effective problem-solving to increase hearing aid use. Both parents and clinicians were accepting of tele-support. Parents and professionals would benefit from technology that allows them to access data logging information more easily and frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…Parents, however, can encounter a multitude of challenges that interfere with hearing aid use, such as gaining confidence with new skills, managing difficult child behavior (e.g., removing hearing aids), and fear about how others may react to their child (Walker et al, 2013;Muñ oz et al, 2015;. Targeted support from their audiologist to purposefully address parents' needs can increase hours of hearing aid use (Muñ oz, Kibbe, et al, 2017).…”
mentioning
confidence: 99%
“…Parents, however, can encounter a multitude of challenges that interfere with hearing aid use, such as gaining confidence with new skills, managing difficult child behavior (e.g., removing hearing aids), and fear about how others may react to their child (Walker et al, 2013;Muñ oz et al, 2015;. Targeted support from their audiologist to purposefully address parents' needs can increase hours of hearing aid use (Muñ oz, Kibbe, et al, 2017).…”
mentioning
confidence: 99%
“…Overall participants had a positive reaction to remote care, and their satisfaction was greatly increased with the use of a web camera during the in-house appointment. A high-level of patient satisfaction was reported in other studies that employed remote hearing aid fitting, adjustment, and support (Penteado et al 2014;Novak et al 2016;Muñoz et al 2017).…”
Section: Intervention Perspectivesmentioning
confidence: 83%
“…Even though most studies included in our review were focussed on adult hearing-aid users, similar teleaudiology services can be easily adopted to benefit CI users, and parents of children who are DHH. One study showed that using a virtual audiologist significantly improved the hearing aid wear time with children (Muñoz et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations